Economic impacts of climate change on cities: A survey of the existing literature - Georgios Stasinopoulos (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
This paper attempts a survey of the existing literature on the direct market impacts of climate change on urban centers. In the first chapter, the argument for the importance of cities as case studies for research on the impacts of climate change is established using current population data and future projections. In the second chapter, a brief overview of how we can go from the global level to the regional level, when we consider the impacts of climate change, is given. In the third chapter, we examine the models and their estimates for the sea level rise impacts on cities. In the fourth chapter, we summarize the impacts of increasing temperature. In the last two chapters, we elaborate on the current limitations and we present some conclusions.
Keywords: 330